2014
DOI: 10.3171/2013.10.peds13291
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative cerebral angiography in arteriovenous malformation resection in children: a single institutional experience

Abstract: Object The use of cerebral intraoperative angiography has been described in resection of arteriovenous malformations (AVMs) in adults. More recently, studies have described experiences with intraoperative angiography in a small number of children. However, data on the safety and clinical utility of intraoperative angiography in the pediatric population remains limited in comparison with available data in adults. The aim of the study was to evaluate the use of cerebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 42 publications
(46 reference statements)
0
25
0
Order By: Relevance
“…While intraoperative and 24-hour postresection angiography represent the gold-standard surgical adjunct, the combination is expensive, invasive, and unavailable at many institutions, such as ours. A recent paper from Gaballah et al 9 demonstrated a 5% complication rate and 14% AVM recurrence rate using intraoperative angiography in the pediatric population. There is, however, a learning curve in using intraoperative Doppler ultrasonography as well as the associated neuronavigation and microscope software to their full potential, and the initial cost of the technology may be prohibitive at some institutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While intraoperative and 24-hour postresection angiography represent the gold-standard surgical adjunct, the combination is expensive, invasive, and unavailable at many institutions, such as ours. A recent paper from Gaballah et al 9 demonstrated a 5% complication rate and 14% AVM recurrence rate using intraoperative angiography in the pediatric population. There is, however, a learning curve in using intraoperative Doppler ultrasonography as well as the associated neuronavigation and microscope software to their full potential, and the initial cost of the technology may be prohibitive at some institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Complete resection rates are all high in the published series, ranging from 80% to 100%. 5,9,13,16,21 We believe the use of intraoperative ultrasound in combination with neuronavigation and integrated operative microscopy is a safe and reliable technique to aid AVM resection in pediatric patients. There are clear advantages in being able to position a smaller craniotomy directly over the intended target lesion: it minimizes blood loss from the craniotomy site and reduces incision length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,9,16 Concern regarding the safety of radiation exposure in children has caused a shift away from studies involving the use of ionizing radiation, such as angiography and CT. 7,22 Recent estimates have placed the mean radiation dose to the skin from a single diagnostic angiogram in a child under the age of 21 at 239.4 mGy, while the dose absorbed by the brain is lower. Infants experience a slightly higher dose due to skull thickness, but the total is still less than 1 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,9,10,16,23,29 Although the underlying cause of this apparently different biology is unclear, 26 it is an important factor to consider in the management and postoperative follow-up of pediatric patients with AVMs. In addition to patient age, deep venous drainage and diffuse nidus have been identified as potential risk factors for recurrence.…”
mentioning
confidence: 99%